CaNRT2.1 Is Required for Nitrate but Not Nitrite Uptake in Chili Pepper Pathogen Colletotrichum acutatum - Kuo, Chia-Chi; Lin, Yung-Chu; Chen, Li-Hung; Lin, Meng-Yi; Shih, Ming-Che; Lee, Miin-Huey (Frontiers in Microbiology, 2021)
Chili peppers are an important food additive used in spicy cuisines worldwide. However, the yield and quality of chilis are threatened by anthracnose disease caused by Colletotrichum acutatum. Despite the impact of C. acutatum on chili production, the genes involved in fungal development and pathogenicity in this species have not been well characterized. In this study, through T-DNA insertional mutagenesis, we identified a mutant strain termed B7, which is defective for the growth of C. acutatum on a minimal nutrient medium. Our bioinformatics analysis revealed that a large fragment DNA (19.8-kb) is deleted from the B7 genome, thus resulting in the deletion of three genes, including CaGpiP1 encoding a glycosylphosphatidyl-inisotol (GPI)-anchored protein, CaNRT2.1 encoding a membrane-bound nitrate/nitrite transporter, and CaRQH1 encoding a RecQ helicase protein. In addition, T-DNA is inserted upstream of the CaHP1 gene encoding a hypothetical protein. Functional characterization of CaGpiP1, CaNRT2.1, and CaHP1 by targeted gene disruption and bioassays indicated that CaNRT2.1 is responsible for the growth-defective phenotype of B7. Both B7 and CaNRT2.1 mutant strains cannot utilize nitrate as nitrogen sources, thus restraining the fungal growth on a minimal nutrient medium. In addition to CaNRT2.1, our results showed that CaGpiP1 is a cell wall-associated GPI-anchored protein. However, after investigating the functions of CaGpiP1 and CaHP1 in fungal pathogenicity, growth, development and stress tolerance, we were unable to uncover the roles of these two genes in C. acutatum. Collectively, in this study, our results identify the growth-defective strain B7 via T-DNA insertion and reveal the critical role of CaNRT2.1 in nitrate transportation for the fungal growth of C. acutatum.